Flux renormalization in constant power burnup calculations. (October 2016) - Isotalo, A.E.; Davidson, G.G.; Pandya, T.M.; Wieselquist, W.A.; Johnson, S.R.
Highlights: Flux renormalized on the substeps of a constant power burnup calculation. New and old renormalization methods are compared. Renormalization significantly improves results with older burnup algorithms. Newer burnup algorithms benefit less due to being more accurate to begin with. Higher order coupling schemes remain more accurate than older burnup algorithms. Abstract: To more accurately represent the desired power in a constant power burnup calculation, the depletion steps of the calculation can be divided into substeps and the neutron flux renormalized on each substep to match the desired power. This paper explores how such renormalization should be performed, how large a difference it makes, and whether using renormalization affects results regarding the relative performance of different neutronics–depletion coupling schemes. When used with older coupling schemes, renormalization can provide a considerable improvement in overall accuracy. With previously published higher order coupling schemes, which are more accurate to begin with, renormalization has a much smaller effect. While renormalization narrows the differences in the accuracies of different coupling schemes, their order of accuracy is not affected.